Effect Analysis on Suspension Exercise Training Combined with Repetitive Transcranial Magnetic Stimulation in the Treatment of Post-stroke Pusher Syndrome - Chuan HU; Xiao YANG; Ying GU; Min LIU; Xin WANG (康复学报)
Objective:To explore the effect of suspension exercise training combined with repetitive transcranial magnetic stimulation (rTMS) on post-stroke pusher syndrome, so as to provide a sustainable and effective training program for the rehabilitation of patients and for returning to family and society as soon as possible.Methods:According to the inclusion and exclusion criteria, 38 patients with post-stroke pusher syndrome who received rehabilitation treatment in hospital rehabilitation center were randomly divided into control group (19 cases) and treatment group (19 cases). The control group was given suspension exercise training of targeted core stability, 30 minutes each time, once a day, six days a week. The treatment group received rTMS on the basis of suspension exercise training to stimulate the motor cortex (M1) of the affected side. Specifically, the midpoint of the intersection of the two coils of the"8"coil was tangent to the skull surface near M1 area of the patient's hemisphere. The intensity was 25%, the threshold was 30%-70%, the frequency was 10 Hz, the stimulation time was 1.5 s, the interval time was 10 s, and each time was about 20 min, once a day, 6 days once a week. The trunk control ability, balance function, body tilt degree and activities of daily living were evaluated by Trunk control test (TCT), Berg balance scale (BBS), scale for contraversive pushing (SCP) and modified Barthel Index (MBI) before treatment, 4 weeks and 8 weeks after treatment.Results:There was no significant difference in TCT, BBS, SCP and MBI scores between the treatment group and the control group before treatment respectively (P> 0.05). After 4 weeks of treatment, the four indexes of the two groups were significantly improved compared with those before treatment (P< 0.001); Except MBI, the scores of TCT and BBS in the treatment group were significantly higher than those in the control group respectively, and the SCP score was significantly lower than that in the control group (P< 0.001); After 8 weeks of treatment, the indexes of the treatment group were significantly improved compared with those before treatment and the control group, the difference was statistically significant respectively (P< 0.001).Conclusion:The combination of suspension exercise training and rTMS can effectively strengthen the core stability of the trunk, correct the tilt state, and increase the balance function and improve the ability of daily life of patients with pusher syndrome. This study shows that suspension exercise training combined with rTMS have a positive role in promoting the treatment of patients with post-stroke pusher syndrome.